Patient-derived cancer modeling for precision medicine in colorectal cancer: beyond the cancer cell line. Issue 6 (2nd June 2020) - Pyo, Dae Hee; Hong, Hye Kyung; Lee, Woo Yong; Cho, Yong Beom
ABSTRACT: Since effective immunotherapeutic agents such as immune checkpoint blockade to treat cancer have emerged, the need for reliable preclinical cancer models that can evaluate and discover such drugs became stronger than ever before. The traditional preclinical cancer model using a cancer cell line has several limitations to recapitulate intra-tumor heterogeneity and in-vivo tumor activity including interactions between tumor-microenvironment. In this review, we will go over various preclinical cancer models recently discovered including patient-derived xenografts, humanized mice, organoids, organotypic-tumor spheroids, and organ-on-a-chip models. Moreover, we will discuss the future directions of preclinical cancer research.